On the equilibria of the restricted four-body problem with triaxial rigid primaries - I. Oblate bodies. (January 2021) - Muhammad, Shah; Duraihem, Faisal Zaid; Zotos, Euaggelos E.
Highlights: We numerically explore the equilibria of the restricted four-body problem with triaxial rigid primaries. We compute the linear stability of the libration points. We determine how the triaxility parameters affect the dynamics of the equilibrium points. Abstract: The equilateral restricted four-body problem, with triaxial rigid oblate bodies, is investigated. Using numerical methods we examine how the linear stability and the positions of the coplanar libration points are affected by the triaxility parameters of the primaries. In each case, we perform a rigorous and systematic analysis for determining the influence of the triaxility parameters σ 1 and σ 2 on the dynamics of the system. Our computations suggest the strong influence of these parameters by revealing additional cases, regarding the total number of equilibria, thus improving the findings of previous related works.